2020
DOI: 10.1111/cas.14317
|View full text |Cite
|
Sign up to set email alerts
|

Application of the microRNA‐302/367 cluster in cancer therapy

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. , glycogen synthase kinase-3β; HCC, hepatocellular carcinoma; HECC, human endometrial carcinoma cell; hESC, human embryonic stem cell; IGF-1R, insulin-like growth factor 1 receptor; iPSCs, induced pluripotent stem cells; JNK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 78 publications
(133 reference statements)
2
15
0
Order By: Relevance
“…We found both miR-302 and miR-367 as prognostic markers from the shared ceRNA network. The miR-302/367 cluster has been previously identified in PRAD-, BRCA-, COAD-, READ-, and UCEC-associated pathways, supporting our findings [41].…”
Section: Discussionsupporting
confidence: 91%
“…We found both miR-302 and miR-367 as prognostic markers from the shared ceRNA network. The miR-302/367 cluster has been previously identified in PRAD-, BRCA-, COAD-, READ-, and UCEC-associated pathways, supporting our findings [41].…”
Section: Discussionsupporting
confidence: 91%
“…We found both miR-302 and miR-367 as prognostic markers from the shared ceRNA network. The miR-302/367 cluster has been previously identified in PRAD, BRCA, COLCA, and UCEC associated pathways supporting our findings [41].…”
Section: Discussionsupporting
confidence: 91%
“…So, miRs are recognized as reliable biomarkers of prognosis and treatment of tumors. [ 12 ] Strongly expressed miR-367 was conducive to the elevation of the sensitivity to therapeutic drug in ovarian cancer. [ 17 ] In this study, we were inspired to explore the possible association of miR-367 in biological processes of BC, and found that previous studies have indicated that several miRNAs such as miR-15a, miR-21, miR-205, miR-342-3p, and miR-520a-5p were associated with a few molecular and clinicopathologic features and poor prognosis in BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] As a key member of the miR-302/367 cluster, miR-367 can play a role in a number of cancers as it prevents cell senescence and death, maintains proliferation signal activation, sabotages growth inhibitors, and modulates cellular biological activities as well as angiogenesis. [ 12 ] Kaid and her colleagues discovered that miR-367 may be a medical target, which can be used as a marker in aggressive embryonal central nervous system tumor and facilitates prognosis and early diagnosis. [ 13 ] Furthermore, miR-367-3p expression levels are closely correlated with International Federation of Gynecology and Obstetrics (FIGO) stage and lymph node metastasis, and high expression of miR-367-3p allows to a high survival rate, oppresses cancer cell metastasis, and quenches the malignant behaviors of tumor in endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%